Exploring the Source of Green Gold - Smith, Ida Dokk (Consilience, 2012)
The global value chain has provided opportunities for artisanal gold mining communities in Colombia to build a mining model based on ecological principles. In the region of El Chocó, Colombia Corporación Oro Verde was established in 1999. The program established a certificate scheme, which is now integrated into the newly developed Fairmined and Fairtrade standard. The label guarantees that the gold is extracted and processed in compliance with social and environmental standards, and without the use of chemicals. In return the miners are offered favorable market access and a 15% premium on top of a guaranteed price. Oro Verde serves as an example of local development from the bottom up, while also illustrating that this development is achieved only when a set of actors works together – from the local to the international level. The challenge ahead is to balance the need for revenue generation activities and increasing production, with environmental considerations.